2012
DOI: 10.1002/elps.201200349
|View full text |Cite
|
Sign up to set email alerts
|

Micellar electrokinetic chromatography: A review of methodological and instrumental innovations focusing on practical aspects

Abstract: This review article addresses recent methodological and instrumental innovations in MEKC with emphasis on practical aspects. Like its predecessors, this review is intended to provide an updated overview covering work on the most salient methodological contributions to enhancing sensitivity and resolution in MEKC-based determinations published over the past two years. The most widespread approaches to enhancing sensitivity, which include improving "classical" online sample concentration techniques, combinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 132 publications
(222 reference statements)
1
43
0
1
Order By: Relevance
“…A good selectivity was obtained by simultaneously adding n-butanol, which can act as cosurfactant, and ethanol, which can widen the electrophoretic window by lowering the EOF. This choice confirmed that solvent-modified MEKC is gaining higher interest with respect to MEEKC due to the higher simplicity of BGE preparation and to the higher stability of micelles with respect to microemulsions [12,32]. In these conditions, the migration order of the peaks was the following: frovatriptan, sumatriptan, rizatriptan, zolmitriptan, almotriptan, naratriptan, indoprofen, and eletriptan.…”
Section: Analytical Target Profile Methods Scouting and Critical Quasupporting
confidence: 57%
“…A good selectivity was obtained by simultaneously adding n-butanol, which can act as cosurfactant, and ethanol, which can widen the electrophoretic window by lowering the EOF. This choice confirmed that solvent-modified MEKC is gaining higher interest with respect to MEEKC due to the higher simplicity of BGE preparation and to the higher stability of micelles with respect to microemulsions [12,32]. In these conditions, the migration order of the peaks was the following: frovatriptan, sumatriptan, rizatriptan, zolmitriptan, almotriptan, naratriptan, indoprofen, and eletriptan.…”
Section: Analytical Target Profile Methods Scouting and Critical Quasupporting
confidence: 57%
“…The improvement obtained with the highest pH and addition of methanol can be explained by the changes in intermolecular interactions that these alterations cause. Lowering the pH affects the localized charge of some analytes and the micelles composition, while addition of methanol alters both the physicochemical properties of the analytes and the micellar medium viscosity and hydrophobicity, besides expanding the migration window by EOF reduction . These conditions alter the solubilities of the amino acids in the micelles, leading to changes in their effective mobilities and thus better resolution .…”
Section: Resultsmentioning
confidence: 99%
“…Owing to similar electrophoretic mobilities of amino acids, CZE usually does not provide appropriate separation. For this purpose, MEKC using SDS as surfactant has been widely used improving the separation by a partitioning mechanism of the analytes between the BGE and the micelle .…”
Section: Introductionmentioning
confidence: 99%
“…Log P values of drugs have been estimated by MEKC [167][168][169] and MEEKC [102,103] since many years. Furthermore, liposome electrokinetic chromatography employing liposomes as pseudostationary phase has been used for the characterization of liposomal drug formulations as well as drug lipophilicity and drug-liposome interactions [170,171].…”
Section: Determination Of Physicochemical Constantsmentioning
confidence: 99%